Classroom reading program to increase children's reading interest at the Emha Ainun Najib (EAN) Yogyakarta library - Suud, Fitriah M.; Azhar, Muhammad; Kibtiyah, Mariah (Community Empowerment, 2021)
The problems faced by partners are the lack of children's interest in reading and the lack of library facilities other than school libraries that are specifically available for children. So that the purpose of this service is to increase children's interest in learning and at the same time facilitate children to be able to use the library around them by providing classroom reading programs. The library was the Emha Ainun Najib (EAN) library in Kadipiro Yogyakarta City which is provided for the general public. This dedication means a lot to children and the local librarian. Children live around the EAN library were more enthusiastic to come and read books in the library. This was due to the pleasant library layout supported by interesting books. This activity was also able to respond to children's curiosity to be more interested in reading so that literacy increases. This service recommends that children's reading rooms need attention, including the types of books that need to be adjusted according to age.